New radiocarbon dates from the Edomite highlands and the hydraulic systems of southern Jordan - Tebes, Juan Manuel (2020)
This study aims to interpret the recent radiocarbon datings of lime-based mortars from hydraulic structures of the archaeological site of as-Sila, in the northern Edomite plateau (Jordan). These radiocarbon dates suggest three main chronological horizons throughout a long period of time, but their interpretation is a difficult task. They present problems related to the nature of the mortar formation and to the discrepancies with the chronology provided by the local pottery, the 14C datings, and the archaeological evidence of other sites in the region. A cautious, interdisciplinary methodologyis thus necessary, one in which the 14C datings are complemented by the contextual archaeological data. Following this approach, we suggest the hydraulic system of as-Sila would have been built during the Iron Age II and later reused during the Persian-Hellenistic and Early-Middle Islamic periods.